La nature inscrite dans les produits - Jean Michel Sorba; Anne Lauvie; Geneviève Michon (Développement Durable et Territoires, 2016)
The article analyses how qualification of products can participate in (re)qualifying environments and resources, based on the examples of honey PDO and cheeses qualifications produced in the Corsican « Maquis ». The various interpretations of this particular environment ignore its uses for production. The article analyses the conditions of its valorization through product qualification processes and selling processes. The first case underlines the objectivation of links between honey and pollen through the bees. The second case underlines the weakness of the association between maquis and cheeses valorization. We conclude on pointing out several obstacles for jointly valorizing environments and products.